Odpowiedzi

2009-09-30T16:14:42+02:00
A) 3=a×2+b
5=a×4+b

3=2a+b /×(-1)
5=4a+b

-3=-2a-b
5=4a+b

-3+5=-2a+4a
5=4a+b

2a=2 /:2
5=4a+b

a=1
5=4+b

a=1
-b=-5+4

a=1
-b=-1 /×(-1)

a=1
b=1

równanie tej prostej to y=x+1

b)3=-2×a+b
-5=4×a+b /×(-1)

3=-2a+b
5=-4a-b

3+5=-2a+(-4a)
5=-4a-b

8=-6a /:(-6)
5=-4a-b

a=-1⅓
5=-4×(-1⅓)-b

a=-1⅓
5=5⅓-b

a=-1⅓
b=-5+5⅓

a=-1⅓
b=⅓

Równanie tej prostej to : y=-1⅓x+⅓

c)0=2×a+b
6=-2×a+b

0=2a+b
6=-2a+b

-b=2a /×(-1)
b=-2a+b

b=-2a
6=-2a+(-2a)

b=-2a
6=-4 /:(-4)

b=-2a
a=-1½

b=-2×(-1½)
a=-1½

b=3
a=-1½

Równanie tej prostej to : y=-1½x+3